Beyond horizontal gene transfer: the role of plasmids in bacterial evolution - Rodriguez-Beltran, J; DelaFuente, J; Leon-Sampedro, R; Maclean, R; San Millan, A (Nature, 2021)
Plasmids have a key role in bacterial ecology and evolution because they mobilize accessory genes by horizontal gene transfer. However, recent studies have revealed that the evolutionary impact of plasmids goes above and beyond being mere gene delivery platforms. Plasmids are usually kept at multiple copies per cell, producing islands of polyploidy in the bacterial genome. As a consequence, the evolution of plasmid-encoded genes is governed by a different set of rules than those affecting chromosomal genes, and these rules are shaped by unusual concepts in bacterial genetics such as genetic dominance, heteroplasmy or segregational drift. In this Review, we discuss recent advances that underscore the importance of plasmids in bacterial ecology and evolution beyond horizontal gene transfer. We focus on new evidence that suggests that plasmids might accelerate bacterial evolution, mainly by promoting the evolution of plasmid-encoded genes, but also by enhancing the adaptation of their host chromosome. Finally, we integrate the most relevant theoretical and empirical studies providing a global understanding of the forces that govern plasmid-mediated evolution in bacteria.